Awareness of ocean literacy principles and ocean conservation engagement among American adults - O’Halloran, Chris; Silver, Mary (Frontiers in Marine Science, 2022)
Ocean literacy influences ocean conservation and might have an impact on sustainable development practices and we investigated the knowledge American adults possess concerning ocean literacy principles and ocean conservation behaviors by asking participants (N=1226) to complete an online survey on ocean literacy principles, health and well-being benefits of time spent in or by the ocean, emotions that result in behavioral change for conservation, and conservation actions. We used a representative sample of the US population by age, gender, and location. The majority of participants were aware of the ocean literacy principle, that the ocean supports a great diversity of life and ecosystems (82%). Calmness, stress reduction, reduced depression, awe, connection with nature, greater life satisfaction, improved happiness, and a feeling of a spiritual connection or refuge were all associated with the ocean environment's emotional health benefits. Monthly beach trips were associated with the physical health benefits of spending time near the ocean. Engagement in ocean conservation action was associated with multiple factors, including awareness of ocean literacy principles (the ocean is largely unexplored, ocean health and human health are connected, and the ocean regulates our climate and weather), monthly visits to the ocean, emotions of sadness and awe, feeling a connection to nature, living 10 miles or less to the ocean, and viewing nature documentaries and Instagram. Findings from this study may provide ideas how to engage the American public in understanding, valuing, and caring for our shared life sustaining ocean.